2019
DOI: 10.1007/s11469-019-00082-5
|View full text |Cite
|
Sign up to set email alerts
|

Addiction to Social Media and Attachment Styles: A Systematic Literature Review

Abstract: Web-based communication via social networking sites (SNSs) is growing fast among adolescents and adults and some research suggests that excessive SNS use can become an addiction among a small minority of individuals. There is a growing body of research that has examined the impact of attachment styles and its influence on internet addiction (more generally) and social media addiction (more specifically). Consequently, the present study systematically reviewed the evidence concerning internet/social media addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 81 publications
4
121
1
1
Order By: Relevance
“…As a new type of behavioral addiction, SNS addiction has received much scholarly attention globally in recent years, and there are numerous studies exploring the risk factors linked to SNS addiction (Marino et al, 2018a,b). Prior studies found that attachment, especially insecure attachment, is closely related to SNS general use and addiction (Blackwell et al, 2017;Monacis et al, 2017;Flynn et al, 2018;Worsley et al, 2018a,b;Chen, 2019;D' Arienzo et al, 2019;Marino et al, 2019). Our results are consistent with prior findings.…”
Section: The Association Between Insecure Attachment Orientation and supporting
confidence: 92%
See 1 more Smart Citation
“…As a new type of behavioral addiction, SNS addiction has received much scholarly attention globally in recent years, and there are numerous studies exploring the risk factors linked to SNS addiction (Marino et al, 2018a,b). Prior studies found that attachment, especially insecure attachment, is closely related to SNS general use and addiction (Blackwell et al, 2017;Monacis et al, 2017;Flynn et al, 2018;Worsley et al, 2018a,b;Chen, 2019;D' Arienzo et al, 2019;Marino et al, 2019). Our results are consistent with prior findings.…”
Section: The Association Between Insecure Attachment Orientation and supporting
confidence: 92%
“…Although SNSs have considerable benefits, excessive use of SNS has been found to have detrimental effects on human behavior (Marino et al, 2018a). Therefore, many scholars have explored factors associated with SNS addiction, among which attachment has received much attention (Blackwell et al, 2017;Monacis et al, 2017;Flynn et al, 2018;Worsley et al, 2018a;Chen, 2019;D' Arienzo et al, 2019;Marino et al, 2019). However, the underlying mechanisms between attachment and SNS addiction remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fredrickson and Roberts, 1997;Aubrey, 2006;Meier and Gray, 2014). In the past few years, the increasing popularity of social media use and the large increase in engagement of adolescents and young people in social networking (Mascheroni and Ólafsson, 2018;D'Arienzo et al, 2019;Gioia and Boursier, 2019) have led researchers to focus on SNS use as a new and highly accessible medium for socializing with self-objectification experiences and OBC (de Vries and Peter, 2013;Fardouly et al, 2015;Manago et al, 2015;Bell et al, 2018;Cohen et al, 2018;Caso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…salience, mood modification, tolerance, withdrawal, relapse, and conflict) to evaluate problematic SNS use (e.g. Griffiths, 2005;Andreassen et al, 2016;Kuss and Griffiths, 2017;Monacis et al, 2017;D'Arienzo et al, 2019). On the contrary, according to a social-cognitive model, researchers have conceptualized problematic online activities in terms of difficulties in impulse control and mood regulation, subsequent negative outcomes resulting from online misuse, and preference for online social interactions, due to a perceived lack of social skills (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Los estilos de apego incluso han sido estudiados en relación con la adicción al internet, encontrándose una relación significativamente positiva entre el estilo de apego inseguro (ansioso y evitativo) y un uso más intensivo y disfuncional de redes sociales, como una manera de reemplazar y compensar los afectos no recibidos del medio cercano del individuo (D'Arienzo, Boursier, & Griffiths, 2019).…”
Section: Investigaciones Sobre Tipos De Apegounclassified